Managing People, Not Just Processes: The Art of Leadership in the Era of Disruption - Firdiansyah Lukman; Giovanni Battista Puteri (PT. Anagata Sembagi Education, 2025)
This study explores the human-centered approach to leadership amid organizational disruption, focusing on how leaders manage people not just processes during times of rapid change and uncertainty. Using a qualitative phenomenological method, the research captures the lived experiences of ten leaders from various sectors, including education, technology, healthcare, and manufacturing. Data were collected through in-depth semi-structured interviews, emphasizing emotional dynamics, leadership values, and interpersonal strategies used by leaders during crisis situations such as the COVID-19 pandemic and digital transformation. The findings reveal that successful leaders prioritize empathy, authentic communication, and psychological safety to maintain team cohesion and morale. Rather than enforcing rigid procedures, they facilitate space for dialogue, reflection, and emotional support. Disruption is not only seen as a threat but also as an opportunity for leadership growth and value transformation. This study underscores the need for leadership development programs that balance technical competencies with emotional intelligence and relational awareness.